Sperm motility is the main problem for honeybee's reproduction both in natural and in artificial insemination. Sperm produced only by sexually mature drone. Drone with high semen volumes can be seen by the external morphology like hairy in back and the existence of yellow stripes on their black abdomen. Semen samples were collected from the drone by the massage technique; these consist of massaging the abdomen of drone. This massage proceeded until penis and semen cream to yellow color, was - Lea Tarliyah; Arief Boediono; Djoko Walujo (Media Veteriner, 1999)
Sperm motility is the main problem for honeybee's reproduction both in natural and in artificial insemination. Sperm produced only by sexually mature drone. Drone with high semen volumes can be seen by the external morphology like hairy in back and the existence of yellow stripes on their black abdomen. Semen samples were collected from the drone by the massage technique; these consist of massaging the abdomen of drone. This massage proceeded until penis and semen cream to yellow color, was produced. Semen taken out with spuit (3 ml) that contain a modification dilution media called "Kiev". Semen samples were collected; volume, abnormalities and motility were measured. The sexually mature drones were observed in 99.06% (213/215) drones with rare hair in back and 76.28% (164/215) with existence of the yellow stripes in the black abdomen. The color of sperm is yellowish white, which is different from mucous that is white. The average volume of semen samples from each drone is 1.11 μl. The average length of sperm is 217.57 μm (107.50-412.50 μm). The average length of sperm is 7,52 μm (5-1O μm). It's flipped tails, broken tails, double tails, and double heads with an average of 19.83%, 12.75%, 6.42%, and 2,25% respectively can determine abnormalities of the sperm. To conduct the artificial insemination, drone sperm should always be available. For this reason sperm should be preserved in an optimal condition storage temperature (5°C, 27 °c and 37°C) and glucose concentration (0%, 0,3%, 0,6%, and 0,9%) containing in the dilution media. This condition can be affecting the sperm motility. The highest motility is achieved when the sperm is kept in 0,9% glucose concentration and storage in 5 °C temperature. In this condition 0.19x106 sperm/ml can survive up to 36 hours. Moreover, the higher concentration of sperm motility up to 36 hours is achieved when sperm is kept in 5 Celsius temperature with different leves of glucose in dilution media. However statistically interaction between glucose concentration and temperature levels does not give significant affects.